The simulation of terahertz waves transmission in the arc plasma - Wang, Hailu; Yao, Jingfeng; Fang, Chuan; Yuan, Chengxun; Li, He-Ping (Frontiers in Physics, 2023)
The diagnostic of high-density hot plasma is a challenging task due to its high temperature and electron density. Arc plasma is one of the typical hot density plasmas, and its diagnosis is the key to develop its new applications. In this paper, the temperature and density distributions of welding plasmas with different discharge currents are numerically simulated based on a Tungsten Inert Gas Arc Welding model, and the electron density distributions are calculated. Then propagation properties of broadband terahertz (THz) waves in the modeling arc jets are calculated by the finite difference time domain method. These results not only provide a preliminary theoretical guidance for in-depth understanding the problems of blackout in re-entry communication, but also develop a new idea for the terahertz diagnostic of plasma with high density.